FIRM SIZE, PENGARUH LEVERAGE, LIKUIDITAS, INVESTMENT OPPORTUNITY SET, PROFITABILITAS TERHADAP EARNINGS QUALITY - Mochammad Aziz Ghoffar; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2023)
This study aims to analyze the effect of firm size, leverage, liquidity, investment opportunity set, profitability on company earnings quality as measured using a modified Penman model.The data used in this study is secondary data with a research population of manufacturing companies listed on the Indonesia Stock Exchange in 2020–2021. This study used a purposive sampling method so that 149 companies were found that met the criteria applied as research variables. Data analysis in this study used descriptive analysis and multiple linear regression with the SPSS version 25 program.The results of this study confirm that firm size and profitability have a significant positive effect on earning quality. However, investment opportunity set and liquidity do not have a significant positive effect on earning quality and leverage does not have a significant negative effect on earning quality.